Otto: a 4.04 GBq (109 mCi) 68Ge/68Ga generator, first of its kind - extended quality control and performance evaluation in the clinical production of [68Ga]Ga-PSMA-11 - Nicole N. Waterhouse; Alejandro Amor-Coarasa; Anastasia Nikolopoulou; John W. Babich (SpringerOpen, 2020)
Abstract Background Here we report on the comprehensive quality control of a 4.04 GBq (109 mCi) generator supplied by itG (Munich, Germany), and used for routine production of [68Ga]Ga-PSMA-11 for clinical imaging. The performance of the 4.04 GBq itG 68Ge/68Ga generator was studied for a year and parameters including elution yield, elution profile, radioactive and stable contaminants were collected. The production yields of a series of 175 [68Ga]Ga-PSMA-11 clinical batches are also reported herein. Results This first-of-its-kind GMP grade 68Ge/68Ga generator from itG with a nominal activity of 4.04 GBq (109 mCi) showed a stable 68Ga elution profile with elution efficiency averaging 58.3 ± 3.7%. 68Ge contaminant in the eluent slightly increased over time but remained 100x lower than those reported for comparable 1.85 GBq (50 mCi) itG generators. Metal impurities were found in concentrations lower than 100 ng/ml (ppb) throughout the study. [68Ga]Ga-PSMA-11 was obtained in 89 ± 4% radiochemical yields and > 99% radiochemical and chemical purities. Conclusion 4.04 GBq (109 mCi) itG 68Ge/68Ga generator is suitable for routinely produced 68Ga tracers used in the clinic. Up to 30% higher amount of final drug product was obtained as compared to the 1.85 GBq (50 mCi) itG generator, and as a result larger number of studies could be performed, while reducing the synthetic burden.